Periodic band formation of Fe(OH)3 precipitate through reaction–diffusion–reaction processes - Hayashi, Hisashi (Frontiers in Physics, 2023)
This paper reports a new class of periodic banding of Fe(OH)3 precipitate through reaction–diffusion–reaction (RDR) processes in agarose gel sandwiched between two metal rods (Ti and Fe) with cyclic alternating voltages. In the RDR processes, electrochemical reactions at metal rods to generate reactant ions, diffusion of the ions influenced by the electric field in the gel, and reactions of the ions to form precipitates were coupled to generate periodic bands of Fe(OH)3 precipitates at the cathode side. The banding morphologies, spatial Fe distribution, and microscopic morphologies of the precipitates were investigated by visual inspection, Fe Kα intensity distribution measurements, and scanning electron microscopy (SEM) observations. The periodic banding strongly depended on the applied voltages, the periods for voltage alternation, the cycle number (NC), and the length of the gel column. Periodic bands resembling Liesegang bands were most clearly observed with high reproducibility for 50 mm gel columns under the applied cyclic alternating voltages of 3 and 1 V for 1 and 4 h, respectively. The number of the periodic bands formed in this system was generally given by NC ‒ NC1 + 1, where NC1 is the cycle number where the first band emerges. These periodic bands contained significant amounts of Fe atoms that were almost uniformly distributed in the agarose gel, strongly supporting the formation of gelatinous Fe(OH)3 precipitates in the bands.